The role of digital marketing in political campaigns - Jeff Chester; Kathryn C. Montgomery (Internet Policy Review, 2017)
Computational politics—the application of digital targeted-marketing technologies to election campaigns in the US and elsewhere—are now raising the same concerns for democratic discourse and governance that they have long raised for consumer privacy and welfare in the commercial marketplace. This paper examines the digital strategies and technologies of today's political operations, explaining how they were employed during the most recent US election cycle, and exploring the implications of their continued use in the civic context. The paper concludes with a discussion of recent policy proposals designed to increase transparency and accountability in digital politics.
Keywords: 300; Elections; Advertising; Privacy; Analytics; Profiling